Numerical analysis of twin-precipitate interactions in magnesium alloys. (1st January 2021) - Siska, Filip; Stratil, Ludek; Cizek, Jan; Guo, Tingting; Barnett, Matthew
Abstract: The present paper performs a two-dimensional numerical study of the interactions between {10 1 ¯ 2} tensile twin and precipitates aligned along basal planes in magnesium alloys. The model consists of an elliptical twin placed in between two rectangular precipitates. Material behavior is modeled using anisotropic elasticity and crystal plasticity. The model represents the situation at the onset of twinning when twins are small and fit in between the precipitates. The results show that precipitates influence the shear stress necessary to accommodate twin by changing the slip critical resolved shear stress (CRSS) values and by acting as obstacles. Thin twins (aspect ratio <0.05) are influenced by both effects while thick twins (aspect ratio >0.1) are influenced by slip CRSS changes. The precipitate thickness plays a crucial role in twin thickening and propagation. Increasing precipitate thickness increases shear stress necessary to accommodate twin and also decreases stress beyond the precipitate which hinders sequential twin propagation. Graphical abstract: Image, graphical abstract